The Impact of Foreign Aid Structure on Jordan’s Economic Growth " 1975-2014" - Masada, Mustafa; Al-Zu’bi, Bashir (Jordan Journal of Economic Sciences, 2020)
This research aims to measure the effect of foreign aid in its various forms and source on Jordan’s economic growth during the period 19752014-, alongside other factors that influence the economic growth. The research adopts both analytical and descriptive approach with quantitative analysis by using Fully Modified Ordinary Least Squares. The study concludes that the impact of foreign aid on Jordan’s economic growth varies depending on aid form and source. In addition for the different characteristics of each of aid and the motives of their submission and the different ways of investing it locally, Leaving differential effects on economic growth and Allowing trade-offs between them. The aid forms a basic pillar of the Jordanian economy and Jordan will continue to rely on it for internal and external reasons, especially in light of the instability in Syria and Iraq and the growing needs of refugees. Jordan also faces the risk of fluctuating foreign aid and unpredictability under global and regional economic slowdown and volatile global oil prices. There is no consensus among economists on the foreign aid role in economic growth, and reached different results ranging from positive and negative impact.